CD154 Induces Matrix Metalloproteinase‐9 Secretion in Human Podocytes. Issue 12 (5th May 2016) - Rigothier, Claire; Daculsi, Richard; Lepreux, Sébastien; Auguste, Patrick; Villeneuve, Julien; Dewitte, Antoine; Doudnikoff, Evelyne; Saleem, Moin; Bourget, Chantal; Combe, Christian; Ripoche, Jean
ABSTRACT: Matrix remodeling is a key feature of glomerulosclerosis secondary to diabetes or hypertension. Podocytes contribute to glomerular basement membrane (GBM) turnover by producing matrix components and matrix remodelling enzymes, including matrix metalloproteinases (MMPs). The CD40/CD154 signaling pathway modulates matrix remodeling through the synthesis of MMPs and tissue inhibitors of MMPs. Platelets are a primary blood reservoir of CD154. Here we studied, the impact of the CD154/CD40 pathway on MMP‐9 expression by cultured human podocytes. The role of CD40/CD154 was evaluated upon exposure of podocytes to recombinant human CD154 (rhCD154) or activated platelet supernatants from healthy human subjects. We first showed by protein and mRNA expression that CD40 was synthesized by podocytes and detectable on kidney tissue sections. CD40 expression was acquired during podocyte differentiation and enhanced upon exposure to rhCD154. In podocytes, rhCD154 induced an increase of MMP‐9 production as shown by RT‐PCR, Western blot and and gelatin zymography. Activated platelet supernatants induced MMP‐9 mRNA synthesis in podocytes, an effect reduced by anti‐CD40 antibody. Our results underscore a potential role for platelets through the CD40/CD154 signaling pathway in the control of GBM synthesis and degradation, via its regulatory role on MMP‐9 production. CD154 secretion by activated platelets may contribute to GBM alterations in proteinuric nephropathies. J. Cell. Biochem. 117: 2737–2747, 2016. © 2016 Wiley Periodicals, Inc. Abstract : CD40 was detectable on kidney tissue sections and synthesized by podocytes upon exposure to recombinant human CD154 or activated platelet supernatants from healthy human subjects. In podocytes, rhCD154 induced an increase of MMP‐9 production. Activated platelet supernatants induced MMP‐9 mRNA synthesis in podocytes, an effect reduced by anti‐CD40 antibody.